Heart rate responses and technical comparison between small- vs. large-sided games in elite professional soccer - Owen, A. L.; Wong, D. P.; McKenna, M.; Dellal, A. (The Journal of Strength and Conditioning Research, 2011)
This study aims to examine the difference in heart rate (HR) responses and technical activities placed upon European elite players when exposed to 2-sided games differing in the number of players and playing area. Fifteen male soccer players from a Scottish Premier League team (26.3 ± 4.85 years, 182.4 ± 6.99 cm, 79.5 ± 8.05 kg, VO2max of 54.36 ± 5.45 ml/kg/min) performed both small (3 vs. 3 plus goalkeepers) and large (9 vs. 9 plus goalkeepers) sided games each lasting for 3 × 5 minutes interspersed with 4-minute passive recovery during the 2009-2010 season. The HR responses and players' technical actions were recorded throughout all sided games. Results show that small-sided games (SSG) induced significantly (p < 0.05, large effect) higher HR responses as compared to large-sided games. Furthermore, during SSGs, players spent significantly longer time in the >85% maximal HR zone (p < 0.05, large effect) as compared to large-sided games. Technical analysis revealed a large practical difference (effect size ranged from 1.5 to 21.2) between small- and large-sided games: less number of blocks, headers, interceptions, passes, and receives but more dribbles, shots, and tackles in SSG. Furthermore, SSG induced significantly lesser total ball contacts per game (p < 0.05, large effect) but significantly greater ball contacts per individual (p < 0.05, large effect) when compared to larger-sided games. The different technical requirements also enable coaches to carry out training games more suitable to specific playing positions such as SSG for midfielders (more dribbles, tackles, and ball contacts per player) strikers (more shots), and large-sided games for defender (more blocks, headers, and interceptions).